2010
DOI: 10.1530/rep-10-0323
|View full text |Cite
|
Sign up to set email alerts
|

Identification of elements in the Smcp 5′ and 3′ UTR that repress translation and promote the formation of heavy inactive mRNPs in spermatids by analysis of mutations in transgenic mice

Abstract: The sperm mitochondria-associated cysteine-rich protein (Smcp) mRNA is transcribed in step 3 spermatids, and is stored in free mRNPs until translation begins w6 days later in step 11. To identify sequences that control the timing of Smcp mRNA translation, mutations in both UTRs were analyzed in transgenic mice using green fluorescent protein (GFP), squashes of seminiferous tubules, and quantification of polysomal loading in adult and 21 dpp testes in sucrose and Nycodenz gradients. GFP fluorescence is first de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 42 publications
2
41
0
Order By: Relevance
“…Four laboratories have reported similar absorbance tracings of extracts of adult testis with a major peak of 80S single ribosomes and a broad hump of polysomes with maximum absorbance in polysomes containing 5-7 ribosomes/polysome [4-6,9,27-29]. Additional file 3, Figure S2, displays an absorbance tracing of 21 dpp testis which is indistinguishable from those of adult testis except that the absorbance peak of the 60S ribosomal subunit is consistently higher than that of 80S ribosomes [4,6]. The opposite is true of adult testis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four laboratories have reported similar absorbance tracings of extracts of adult testis with a major peak of 80S single ribosomes and a broad hump of polysomes with maximum absorbance in polysomes containing 5-7 ribosomes/polysome [4-6,9,27-29]. Additional file 3, Figure S2, displays an absorbance tracing of 21 dpp testis which is indistinguishable from those of adult testis except that the absorbance peak of the 60S ribosomal subunit is consistently higher than that of 80S ribosomes [4,6]. The opposite is true of adult testis.…”
Section: Resultsmentioning
confidence: 99%
“…However, the size of polysomes translating the Ldhc mRNA is reduced based on differences in the number of fractions separating free-mRNPs and polysomes in purified cells and freshly dissected testis, 1 vs. 3-4 [4]. The Northern blot also demonstrates that polysomal Pgk2 mRNA is undetectable in pachytene spermatocytes purified from 16 day prepubertal testes, an age which contains no round spermatids [30].…”
Section: Resultsmentioning
confidence: 99%
“…To better understand mRNA assembly into and release from mRNPs in spermatids, a series of transgenic mice have been generated that contain a reporter gene (GFP or hGh) with various 5′ and/or 3′ UTRs, including those from translationally controlled mRNAs. Analyses of these transgenes revealed that mRNAs expressed in spermatids can undergo sequence-independent assembly into translationally-repressed mRNPs [68], and that specific sequences in the UTRs of Scmp and Prm1 participate in controlling the timing of mRNA release from mRNP particles and association with ribosomes [9295]. Studies by Braun and colleagues identified two sequences in the Prm1 3′UTR that can delay translation of a reporter mRNA, including a translational control element (TCE) and a Y-box recognition sequence (YRS, UCCAUCA) that is recognized by Y-box proteins (discussed below) [9497].…”
Section: Complexity and Post-transcriptional Regulation Of The Devementioning
confidence: 99%
“…Studies by Kleene and colleagues revealed a role for uORFs in translational control during spermiogenesis while demonstrating that both the 5′ and 3′ UTRs of Smcp are required to recapitulate the strength and duration of translational control observed with endogenous Smcp mRNAs [92, 93]. Additional evidence that 5′UTRs can influence translation of germ cell transcripts in spermatids comes from the analysis of alternative mRNAs derived from the AKAP4, TBP, and SOD1 genes.…”
Section: Complexity and Post-transcriptional Regulation Of The Devementioning
confidence: 99%
“…145 In the presence of very clear data outlining the importance of histone biology and the testis-specific nature of several of the key proteins involved in this exchange, researchers are exploring the potential value of this pathway in contraceptive development. 143,147 In parallel with the exchange of histones for protamines, the sperm head is being sculpted into its speciesspecific shape. 146 The commencement of spermiogenesis is associated with a massive wave of transcriptional activity involving the activation of a variety of postmeiotic genes in haploid cells.…”
Section: The Sperm Headmentioning
confidence: 99%